‘Motherhood in childhood’: Generational change in Ethiopia - Crivello, G; Boyden, J; Pankhurst, A (Lectito, 2019)
This article explores the changing place of ‘motherhood’ in the lives of girls and young women in Ethiopia, from a generational, life course perspective. It focuses on ‘motherhood in childhood’ in the context of rapid social change, drawing on multi-generational narratives from young women, their mothers and grandmothers, as part of Young Lives, a fifteen-year study that has traced the life trajectories of a group of girls growing up in poverty. Marriage and motherhood in childhood in past generations was the norm but has increasingly come to be seen as incompatible with the expectations for modern female childhood. A growing discourse of female empowerment suggests significant expansion of ‘choice’ for girls, but closer inspection of girls’ lived experiences of marriage and motherhood suggests a more complex, uneven, picture. Girls face multiple, sometimes contradictory messages regarding the kinds of respectable life paths they should pursue. Their sense of expanded horizons in childhood is easily diminished when they become young mothers, highlighting the persistent influence of poverty and the feminisation of reproductive roles and the ambiguous nature of their agency across time.